SINTESE, CARACTERIZAÇÃO, ANALISE CONFORMACIONAL E ATIVIDADE ANTIOXIDANTE DE ANALOGOS DE CHALCONAS BROMADAS E HIDROXILADAS - Sens, Larissa (2014)
This study presents theoretical results regarding the conformational equilibrium of three diferent chalcones CHALBr (2-propen-1-one, 1-(2-bromophenyl)-3-phenyl), CHALOH (2-Propen-1-one, 3-(4-hydroxyphenyl)-1-phenyl) and CHALBrOH (2-Propen-1-one, 1-(2- bromophenyl)-3-(4-hydroxyphenyl).